ANALYSIS OF ORGANIZATIONAL CULTURE STUDIES IN TURKEY (Third Sector Social Economic Review, 2022)
The aim of this study is to compile the articles about organizational / school culture published in Turkey in educational sciences and to present a holistic view to them. In this study, descriptive content analysis, one of the descriptive survey model and content analysis, was used. The data source of this study consists of the articles on organizational or school culture published between 2003 and 2019 in TR Index created by ULAKBİM. After the determined criteria and the examination of contents of articles, the sample of the study consists of 38 articles conducted in Turkey, open access and without limitations. In this study, categorical analysis technique, one of the content analysis types, was used. When the articles on organizational / school culture are generally examined,, it is seen that there has been an increase in number of publications after 2013, publications were generally carried out with two authors and often studied at primary education level, organizational/school culture and organizational behaviour were mostly examined, quantitative research methodology were used very dominantly and depending on this methodology, correlational survey model studies were often carried out, mostly survey was used as data collection tool. It is considered very important to include more organizational/school culture studies at higher education level, to use qualitative research methods and designs more, and accordingly to obtain in-depth data with data collection methods and techniques such as interview, observation, metaphor and vignette.
Keywords: Organizational culture; School culture; Thesis; Descriptive content analysis; Categorical analysis technique